Compact Wilkinson Power Divider with Common Inductor on the IPD Process - Pakasiri, Chatrpol; Wang, Sen (My University, 2021)
This paper presents a Wilkinson power divider using a common inductor. The lumped topology uses the inherently inductive loss of the inductor as a part of the design, so the conventional resistor for high isolation can be omitted. Therefore, low-loss and high-isolation performances of the compact circuit were achieved. The proposed 2.5-GHz divider was implemented on a silicon-based integrated passive device process. Measurement of the prototype chip had a reflection coefficient below 18 dB at all ports, an insertion loss of 0.5 dB and isolation above 28 dB. The chip size is merely 0.011λ o× 0.019λ o.
Keywords: Common inductor; Integrated passive devices; Lumped transmission line; Resistorless; Wilkinson power divider